Análisis multicriterio de la susceptibilidad de propagación de incendios forestales en el Parque Nacional Natural El Tuparro (2025)
This document covers the fire hazard zoning of the vegetation cover of El Tuparro National Natural Park through a spatial model in a geographic information system applied to the multicriteria evaluation method. For this, the characterization of the variables that influence the threat of forest fire occurrence is carried out, in order to determine the potential fire zones in PNN El Tuparro.